Effect of transferrin glycation induced by high glucose on HK-2 cells in vitro - Ma, Yanqi; Zhou, Qikai; Zhao, Pingping; Lv, Xiaoyu; Gong, Caixia; Gao, Jie; Liu, Jingfang (Frontiers in Endocrinology, 2023)
Background and objective:Glycation is a common post-transcriptional modification of proteins. Previous studies have shown that advanced-glycation end modified transferrin (AGE-Tf) levels in diabetic rat kidney tissues were increased; however,its role in diabetic nephropathy remainsunclear.In this study,differencesinglycation degree and Tf sitesinduced by differinghigh glucose concentrations invitroand effect on total iron binding capacity (TIBC) were observed.Moreover, the effect of AGE-Tf on human renal tubular epithelial cells (HK-2) was investigated. Methods:invitroTf was incubated with increasing glucoseconcentrations (0mM, 5.6mM, 11.1mM, 33.3mM, 100mM, 500mM, 1000mM) forAGE-Tf. DifferencesinAGE-Tfglycation degree and TIBC level were analyzed via colorimetric method. The AGE-tf glycation sites were identified withLC-MS/MS.HK-2 cells were treated with AGE-Tf prepared with different glucose concentrations (33.3mM and 500mM) in vitro.The effects of AGE-Tf on HK-2 cell viability, proliferation, oxidative stress index, and Tf receptor expression levels were then observed. Results:With increasingglucose concentrations (100mM, 500mM and 1000mM) invitro,Tfglycation degree was significantly increased.The TIBC levels of AGE-Tfwere decreased significantly withincreasing glucose concentrations(33.3mm,100mM,500mM,and1000mM).Fourglycated-modification sites in Tf, and17 glycated-modification sites were detected in AGE-Tf (500mM) by LC-MS/MS.The structural types of AGEs were CML, G-H1, FL-1H2O, FL, and MG-H1.No significant differenceswerefound in the survival rate of HK-2 cells amongAGE-Tf (500mM),AGE-Tf (33.3mM), and Tf groups (all P>0.05).The apoptosis rate of HK-2 cells in the AGE-Tf (500mM) group was significantly higher than that in the AGE-Tf (33.3mM) group.Additionally,both of them were significantly higher than that in the Tf group (both P<0.05).The MDA levels of HK-2 cells in AGE-Tf (500mM) and AGE-Tf (33.3mM) groups were higher but not significantly, than that in the Tf group(both P>0.05).The T-AOC level of HK-2 in AGE-Tf (500mM) group was significantly lower than that in the AGE-Tf (33.3mM) and Tf groups (both P<0.001).The GSH level of HK-2 cells in AGE-Tf (500mM) group was significantly lower than that in Tf group (P<0.05).The expression level of TfR in AGE-Tf (500mM) group wasalso significantly lower than that in the Tf group (P<0.05). Conclusion: The degree and sites of Tfglycation wereincreased invitrosecondary tohigh-glucose exposure; however,the binding ability of Tf to iron decreased gradually.After HK-2 wasstimulatedby AGE-Tf invitro, the apoptosis of cells was increased,antioxidant capacity decreased, and TfR expression levels weredownregulated.